2008
DOI: 10.1086/586896
|View full text |Cite
|
Sign up to set email alerts
|

Microlensing Search for Planets with Two Simultaneously Rising Suns

Abstract: Among more than 200 extrasolar planet candidates discovered to date, there is no known planet orbiting around normal binary stars. In this Letter, we demonstrate that microlensing is a technique that can detect such planets. Microlensing discoveries of these planets are possible because the planet and host binary stars produce perturbations at a common region around center of mass of the binary stars and thus the signatures of both planet and binary can be detected in the light curves of high-magnification mic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…What is immediately noticeable from the animations is the fact that often the ABb system is well-approximated by a superposition of the AB and Ab systems, at least in parts of the caustic, as has been previously noted by Han (2008b) and similarly noted for multiplanet systems by Gaudi et al (1998) and Han et al (2001). In fact, the ABb caustics appear to largely follow the three topologies of double-lens planetary microlensing, though see Daněk & Heyrovský (2015a) for a more precise definition of the multiple possible topologies of triple lenses.…”
Section: Superposition Self-intersection and Metamorphosessupporting
confidence: 64%
See 2 more Smart Citations
“…What is immediately noticeable from the animations is the fact that often the ABb system is well-approximated by a superposition of the AB and Ab systems, at least in parts of the caustic, as has been previously noted by Han (2008b) and similarly noted for multiplanet systems by Gaudi et al (1998) and Han et al (2001). In fact, the ABb caustics appear to largely follow the three topologies of double-lens planetary microlensing, though see Daněk & Heyrovský (2015a) for a more precise definition of the multiple possible topologies of triple lenses.…”
Section: Superposition Self-intersection and Metamorphosessupporting
confidence: 64%
“…4 To date, only one microlensing event has been claimed to be caused by a circumbinary planet, MACHO-97-BLG-41L (Bennett et al 1999), but this was later shown to be caused by binary stars with orbital motion (Albrow et al 2000;Jung et al 2013;Han et al 2016). There have been no other microlensing circumbinary planet detections published, and relatively little theoretical work on microlensing by circumbinary planets, with only a brief paper by Han (2008b) addressing them directly. By assuming that circumbinary planets would be most detectable when the size of the central caustics of the binary and planet were similar, Han (2008b) esti-mated the range of planet and binary separations for which the microlensing technique is efficient at detecting circumbinary planetary systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the microlensing technique should be able to identify circumstellar giant planets in binary systems 100 AU (Lee et al 2008), or Jupiter-mass circumbinary planets orbiting binaries separated by ∼0.15-0.5 AU (Han 2008). In the future, microlensing searches may thus enrich the samples of planets residing in and around (moderately) close binaries.…”
Section: Observational Methods To Detect Extrasolar Planets In Binarymentioning
confidence: 99%
“…Lensing by a binary star with a planet has been explored less frequently Lee et al 2008;Han 2008a;Chung & Park 2010). In view of the two recently detected systems, this is bound to change.…”
Section: Introductionmentioning
confidence: 99%